Penyuluhan Kerupuk Tulang Ikan Bandeng kepada Kaum Ibu di Desa Batuphat Timur Lhokseumawe-Aceh - Rachmawati Rusydi; Salamah; Mainisa Mainisa; Munawwar Khalil (Forum Kerjasama Pendidikan Tinggi, 2021)
Batuphat Timur village has several potential for their fish product. From milkfish and shrimp, especially for their woman empowerment. However, this product is not utilized optimally in the community. This community service aimed to socialize the utilization of milkfish bone as fishery waste to make fish bone snack for the women at Batuphat Timur village, Muara Satu District, Lhokseumawe. The steps of this community service consisted of preparing survey quetionare for understanding level and explaining the information of aquatic product specifically fish bone snack. This service resulted positive impact in increasing the knowledge of the women in that village about processed fish bone snack. Generally, the percentage of the women of East Batuphat village which understood about fishery processed product and fish bone snack development increased significantly after implementing the socialization.